Analyzing barriers to implementing industrial symbiosis networks using DEMATEL - Bacudio, Lindley R. (Animo Repository, 2016)
Industrial symbiosis (IS) is a mechanism by which increased sustainability (e.g., lower carbon emissions, lower resource consumption) can be achieved through the establishment of symbiosis networks which result in more efficient material and energy use. IS networks are formed through a long process of planning wherein potential synergies between candidate component plants are identified and evaluated for feasibility. Therefore, a systematic design approach is needed to facilitate the successful implementation of these networks. However, the first step is to properly identify potential barriers (e.g., lack of effective communication, confidentiality issues, support services) to success. In this work, barriers to implementing IS in an industrial park are analyzed using Decision Making Trial and Evaluation Laboratory (DEMATEL). DEMATEL is an approach for identifying cause-effect relationships among several factors in order to understand the problem properly. The results from this study can then be used by stakeholders to create policies which focus on addressing the fundamental barriers towards forging sustainable IS networks. © 2016 The Institution of Chemical Engineers.